MATCHING GAME IN TEACHING READING COMPREHENSION AT MTS MATSARATUL HUDA PAMEKASAN - Yuliarsih Yuliarsih; Evha Nazalatus Sa’adiyah (INTERAKSI : Jurnal Kependidikan, 2018)
This study aims to describe the implementation of matching game in teaching reading comprehension at eight grade students of Mts Matsaratul Huda Pamekasan. This study is descriptive qualitative research, and the subject of this study are the eight grade students of Mts Matsaratul Huda Pamekasan. The data were collected by using observation, interview, and documentation. In analyzing the data, there are some steps. The first is identifying the kind of students’ motivation. The second is identifying students speaking ability. The next step is classifying the data that had been collected and analyzing the data referring to be selected theory. The last is taking conclusion. The result of this study showed the teacher implemented matching game by put the students into several groups and gave each group random sentence to make paragraph, after that the groups shared their paragraph with other to make complete story. Matching game included in both competitive and cooperative game of kind of games. Matching game makes students active and interactive in the class to share, responsible with the other, allow expressing their feelings about the topic, and they get new vocabulary and easily being memorized.